Relationships between deforestation in the state of Bahia from 2004 to 2019 and the new forest code Lei-12.651/2012 - Araujo, Ralph Wendel Oliveira de (2022)
Deforestation is a current and worrying topic because it is entirely associated with environmental imbalance, such as affecting the climate, causing an increase in the emission of CO2 into the atmosphere, in addition to causing the destruction of species of fauna and flora. Law 12.651/2012, also known as the new forest code, designated instruments in which it indicates how and where Brazilian native vegetation can be exploited and which areas must remain preserved. One component that was included in the new forest code was the Rural Environmental Registry (CAR) in order to reduce illegal deforestation. According to the Map Biomas database, from 2012 to 2019 there was a reduction in deforestation in the state of Bahia, when compared to the years from 2004 to 2011. This was due to the greater commitment of Organs responsible bodies, especially the Environment and Water Resources Institute (INEMA), involving strategic actions such as forest monitoring with a team of experts in geoprocessing to collect data on vegetation decrement and thus plan inspection operations, also in conjunction with other bodies. However, despite the evolution, the deforested area is still absurdly extensive, and has been directly affecting all the biomes present in the state's territory. One of the major factors that contribute to this deforestation is the use of the area for agricultural activities and the poor adherence to CAR by rural landowners, not complying with the rules imposed by it.